ANALISIS PELAYANAN PAKET POS DI KANTOR POS JALAN SUDIRMAN PEKANBARU - Yesran Sanrova Tamba; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Services City Post Office Pekanbaru in the delivery of postal parcels has not done well so that users of postal services increasingly in decline, as well as delivery service parcel post still tend to wait for delivery of packages simultaneously, which is known delivery postal packets that will be sent must wait for the fulfillment of capacity car will bring the package so that it is experiencing delays in delivery, as well as the lack of precision of acceptance parcel post which is known in the service time that is later than the delivery until the receipt of postal package. The purpose of this study was to determine the factors that affect the implementation of the Parcel Post services at the Post Office Jalan Sudirman Pekanbaru and to know the Post Office services provided Jalan Sudirman Pekanbaru in the delivery of postal parcels.The type and method of research is descriptive research, which is defined as the process of solving problems investigated by presenting or describing the state of the subject and object of research at the present time based on the facts that appear or as it is. In the data collection authors conducted in-depth interviews and searches documents and archives post office.The results showed that there are several factors that influence the Parcel Post services at the Post Office street Sudirman Pekanbaru is the factor Speed, Accuracy, Ease of Justice which directly affect services provided by the post office. Services provided post offices by establishing standard operating procedures that have been established by the time service delivery, clear procedures as well as the cooperation of employees between superiors and subordinates, it is the service provided has been running well where people have received services provided by the post office even though sometimes the waiter given still slow due to the lack of the number of employees in providing services and lack of infrastructure available so that the service provided is not timely, but the post office will remain optimal in providing services to visitors post office.Keywords: Analysis, Public Service, Postal Package delivery